Statistical review of the insulation capacity of the Geiger-Muller counter - Obrenović Marija D.; Janićijević Aco J.; Arbutina Dalibor S. (Nuclear Technology and Radiation Protection, 2018)
This work considers the manifestation of spontaneous breakdowns of Geiger-Mueller counters. This is an experimental type of work. The reasons leading to the spontaneous breakdowns of Geiger-Mueller counters have been analysed under controlled laboratory conditions. The experiments were carried out under the “constant voltage”. The tested Geiger-Mueller chambers were commercial chambers of the radial electric field and homogenous electric field. The experimental-statistical methods were used in order to choose the chambers with identical features (with 0.1 % of statistical reliability).The results of experiments showed that the spontaneous breakdown of the Geiger-Mueller counter happens even in the conditions of shielding. They also showed that those breakdowns have cumulative features. The reason for that is a positive feedback between the spontaneous breakdowns. The explanation is confirmed and quantified by the working gas filtering experiments. [Project of the Serbian Ministry of Education, Science and Technological Development, Grant no. 171007]